2019
DOI: 10.1080/2575517x.2019.1617575
|View full text |Cite
|
Sign up to set email alerts
|

Manifesto for an international digital mental health network

Abstract: Current mental health services across the world remain expert-centric and are based on traditional workflows, mostly using impractical and ineffective electronic record systems or even paper-based documentation. The international network for digital mental health (IDMHN) is comprised of top-level clinicians, regulatory and ICT experts, genetic scientists, and support organizations. The IDMHN has been formed to enable the implementation of digital innovations in clinical practice, hereby facilitating the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Multiple recent reviews for delivering mental health care via digital technologies have shown that these are safe, feasible and effective among groups of people with mental health disorders [7][8][9][10][11][12][13]. Furthermore, digital technologies have the potential to improve mental health care systems, increase system capacity and transparency [14], enable data collection for monitoring and measure health outcomes, facilitate data sharing among health services [15,16], enhance access in rural and remote areas [17][18][19][20], and improve rationing of costs and human resources [14,16]. The integration and reimbursement of digital technology tools at different levels of the health systems depends on the performance and capacity to meet health system objectives such as quality, accessibility, efficiency and equity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent reviews for delivering mental health care via digital technologies have shown that these are safe, feasible and effective among groups of people with mental health disorders [7][8][9][10][11][12][13]. Furthermore, digital technologies have the potential to improve mental health care systems, increase system capacity and transparency [14], enable data collection for monitoring and measure health outcomes, facilitate data sharing among health services [15,16], enhance access in rural and remote areas [17][18][19][20], and improve rationing of costs and human resources [14,16]. The integration and reimbursement of digital technology tools at different levels of the health systems depends on the performance and capacity to meet health system objectives such as quality, accessibility, efficiency and equity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health disorders today account for more years lived with disability (YLDs) than any other health condition, with close to 30% of all people worldwide having a mental health disorder at one point during their lifetimes [ 1 , 2 ]. Children and adolescents are particularly vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…Other future developments in the field include the evaluation of the role of rare variants and more robust estimations of pharmacogenetic testing cost-effectiveness in clinical practice. A comprehensive predictive model including clinical predictors may the then be hypothesized as a valuable support tool for clinicians [44], ideally integrated in electronic health records [45]. Routine clinical implementation, particularly when more extensive genotyping will be performed, will however have to face a number of management and ethical issues.…”
Section: Discussionmentioning
confidence: 99%